Cultural-Based Comics for Learning Equation of Straight Line and System of Linear Equation in Two Variables - Jayanti, Meidy; Wiratomo, Yogi (Journal of Mathematical Pedagogy (JoMP), 2019)
The aim of this research is to develop cultural-based comic-based mathematics teaching materials. This research was conducted on 8th grade students of junior high schools precisely at Al Ma'ruf Islamic Middle School, Al Wahyu MTs, and Madrasah Tsanawiyah Insan Kamil. This study used research and development methods with the ASSURE model. In this study, the products were tested on material experts (lecturers), material experts (teachers), linguists, development experts, graphic design experts, 3 students selected from 3 schools for one to one test, 15 students from 3 schools for a small group test, and 20 students from 1 school for a large group to test the effectiveness of the product. This product test used the ttest to obtain ttest is 8.225 and ttable is 2.093 or ttest mpre than t table. Then it can be concluded that there is an effective use of mathematics comic teaching materials between pre test and post test scores and can be categorized as feasible.Keywords: Teaching Materials, Math Comics, Culture.